OPTIMALISASI MODEL PEMBELAJARAN RADEC TERHADAP HASIL BELAJAR PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI: Optimizing the RADEC Learning Model to Improve Learning Outcomes in Islamic Religious Education and Character Education - Dinda Agustina; A. Fatoni; Waluyo Erry Wahyudi (STAI Ma'had Aly Al-Hikam Malang, 2026)
article aims to determine the effect of implementing the RADEC (Read, Answer, Discuss, Explain, and Create) model on student learning outcomes in the subject of Islamic Religious Education and Character Education (PAI-BP). This article employs a quantitative approach, utilizing a quasi-experimental method with a post-test-only control group design. The research subjects were seventh-grade students at SMP Negeri 7 Mesuji Lampung. The experimental class implemented the RADEC model, while the control class used the Direct Instruction model. The research instrument consisted of a multiple-choice test that had been validated and was reliable. The results of the normality test indicated that the data were not normally distributed; therefore, data analysis was conducted using the nonparametric Mann–Whitney test. The results of the hypothesis test showed an Asymp. Sig. (2-tailed) value of 0.001 (p < 0.05), indicating a significant difference in learning outcomes between the experimental and control classes. This implies that the implementation of the RADEC model has a significant impact on improving student learning outcomes in the PAI-BP subject, particularly in terms of higher-order thinking skills at level C5 (Evaluation) in Bloom’s Taxonomy. Artikel ini bertujuan mengetahui pengaruh penerapan model RADEC (Read, Answer, Discuss, Explain, and Create) terhadap hasil belajar peserta didik pada mata pelajaran Pendidikan Agama Islam dan Budi Pekerti (PAI-BP). Artikel ini menggunakan pendekatan kuantitatif dengan metode quasi eksperimen melalui desain post-test only control group. Subjek penelitian adalah siswa kelas VII SMP Negeri 7 Mesuji Lampung. Kelas eksperimen menerapkan model RADEC dan kelas kontrol menggunakan model Direct Instruction. Instrumen penelitian berupa tes pilihan ganda yang telah diuji validitas dan reliabilitasnya. Hasil uji normalitas menunjukkan data tidak berdistribusi normal sehingga analisis data dilakukan menggunakan uji nonparametrik Mann–Whitney. Hasil uji hipotesis menunjukkan nilai Asymp. Sig. (2-tailed) sebesar 0,001 (p < 0,05), yang berarti terdapat perbedaan hasil belajar yang signifikan antara kelas eksperimen dan kelas kontrol. Artinya, penerapan model RADEC berpengaruh signifikan dalam meningkatkan hasil belajar siswa pada mata pelajaran PAI-BP, khususnya pada kemampuan berpikir tingkat tinggi level C5 (Evaluasi) dalam Taksonomi Bloom. Kata Kunci : Budi Pekerti; Hasil Belajar; Model Pembelajaran; Pendidikan Agama Islam; RADEC.